Effect of betaine on growth performance and carcass traits of meat ducks - WANG Yi-zhen (浙江大学学报. 农业与生命科学版, 2000)
The study was conducted to examine the effects of betaine on growth and carcass characteristics of meat ducks. Day-old commercial strain Cherry Valley meat ducks (n=690) were randomly allocated into five groups for a six-week feeding trial. Five dietary levels of betaine supplementation were arranged for each of the two experimental periods: the growing ducks (1-21 d) at 0, 500, 1 000, 1 500 and 2 000 mg/kg diet, and the finishing ducks (22-42 d) at 0, 250, 500, 750 and 1 000 mg/kg of diet. At the end of the feeding trial, 90 ducks (18 ducks per group) were selected to determine the carcass traits. Liver and breast muscle samples were also collected. For growing ducks, betaine supplementation (500 2 000 mg/kg) significantly increased average daily gain (ADG) (P<0.01). It also increased average daily feed intake (ADFI) (P<0.01) except for group 4 at 2 000 mg/kg as compared with the control group. However, such an increase did not significantly influence the feed-to-gain ratio (P>0.05). During the finishing period, ADG increased linearly and the feed-to-gain ratio decreased linearly with increasing betaine levels. Betaine supplementation at 750 mg/kg and 1 000 mg/kg improved ADG (P<0.05). Betaine supplementation at 1 000 mg/kg also significantly decreased the feed-to-gain ratio. Analysis of carcass traits indicated that betaine could increase the percentage of breast muscle (P<0.01) and decrease the percentage of abdominal fat (P<0.01) as compared with the control group. Betaine at 1 000 mg/kg increased the total and specific activities of betaine-homo-cysteins-methyltransferase (P<0.01), increased the content of free carnitine in the liver (P<0.01) and of acid insoluble carnitine in the breast muscle (P<0.01). These results imply that betaine could enhance synthesis of carnitine by improving methylation metabolism and stimulate β-oxidation of long chain fatty acids in the inner mitochondria membrane of muscle cells.